High capacity reversible hiding in encrypted domain based on cipher-feedback secret sharing - Minqing ZHANG; Chao JIANG; Fuqiang DI; Zongbao JIANG; Xiong ZHANG (Tongxin xuebao)
To improve the security, robustness and embedding rate of reversible hiding in encrypted domain in the distributed environment, a multiple embedding algorithm based on cipher-feedback secret sharing was proposed.Firstly, the additional data were embedded into the polynomial coefficients redundancy generated in the process of secret image sharing.Secondly, the extra secrets were embedded by using the additive homomorphism of secret sharing.Experimental results demonstrate that a better security and robustness has been obtained by improving the diffusion characteristic of secret sharing using the feedback mechanism.In the (3,4) and (3,5) threshold, the embedding rates can reach 6.00 bit per pixel and 4.80 bit per pixel respectively.The proposed algorithm can not only maintain the strong security and separability, but also obtain a better embedding capacity.Meanwhile, the embedding rate of the scheme is not affected by the carrier image and is only related to the selection of algorithm parameters.